Optimization of printing techniques for electrochemical biosensors - Zainuddin, Ahmad Anwar; Mohd Mansor, Ahmad Fairuzabadi; Ab Rahim, Rosminazuin; Nordin, Anis Nurashikin (AIP, 2017)
Electrochemical biosensors show great promise for point-of-care applications due to their low cost, portability and compatibility with microfluidics. The miniature size of these sensors provides advantages in terms of sensitivity, specificity and allows them to be mass produced in arrays. The most reliable fabrication technique for these sensors is lithography followed by metal deposition using sputtering or chemical vapor deposition techniques. This technique which is usually done in the cleanroom requires expensive masking followed by deposition. Recently, cheaper printing techniques such as screen-printing and ink-jet printing have become popular due to its low cost, ease of fabrication and mask-less method. In this paper, two different printing techniques namely inkjet and screen printing are demonstrated for an electrochemical biosensor. For ink-jet printing technique, optimization of key printing parameters, such as pulse voltages, drop spacing and waveform setting, in-house temperature and cure annealing for obtaining the high quality droplets, are discussed. These factors are compared with screen-printing parameters such as mesh size, emulsion thickness, minimum spacing of lines and curing times. The reliability and reproducibility of the sensors are evaluated using scotch tape test, resistivity and profile-meter measurements. It was found that inkjet printing is superior because it is mask-less, has minimum resolution of 100 μm compared to 200 μm for screen printing and higher reproducibility rate of 90% compared to 78% for screen printing.